Electron microprobe and LA-ICP-MS data of melt inclusions, volcanic glass, magmatic sulphides and Fe-Ti oxides from Brothers volcano, Kermadec arc (SONNE cruise SO135) - Manuel Keith; Karsten M Haase; Reiner Klemd; Daniel J Smith; Ulrich Schwarz-Schampera; Wolfgang Bach (PANGAEA, 2020)
Most magmatic-hydrothermal Cu deposits are genetically linked to arc magmas. However, most continental or oceanic arc magmas are barren, and hence new methods have to be developed to distinguish between barren and mineralised arc systems. Source composition, melting conditions, the timing of S saturation and an initial chalcophile element-enrichment represent important parameters that control the potential of a subduction setting to host an economically valuable deposit. Brothers volcano in the Kermadec island arc is one of the best-studied examples of arc-related submarine magmatic-hydrothermal activity. This study, for the first time, compares the chemical and mineralogical composition of the Brothers seafloor massive sulphides and the associated dacitic to rhyolitic lavas that host the hydrothermal system. Incompatible trace element ratios, such as La/Sm and Ce/Pb, indicate that the basaltic melts from L extquotesingleEsperance volcano may represent a parental analogue to the more evolved Brothers lavas. Copper-rich magmatic sulphides (Cu > 2 wt%) identified in fresh volcanic glass and phenocryst phases, such as clinopyroxene, plagioclase and Fe–Ti oxide suggest that the surrounding lavas that host the Brothers hydrothermal system represent a potential Cu source for the sulphide ores at the seafloor. Thermodynamic calculations reveal that the Brothers melts reached volatile saturation during their evolution. Melt inclusion data and the occurrence of sulphides along vesicle margins indicate that an exsolving volatile phase extracted Cu from the silicate melt and probably contributed it to the overlying hydrothermal system. Hence, the formation of the Cu-rich seafloor massive sulphides (up to 35.6 wt%) is probably due to the contribution of Cu from a bimodal source including wall rock leaching and magmatic degassing, in a mineralisation style that is hybrid between Cyprus-type volcanic-hosted massive sulphide and subaerial epithermal–porphyry deposits.